2016
DOI: 10.3390/ijerph13050511
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Perfluoroalkyl Substances and Behavioral Development in Children

Abstract: Background: In recent years, prevalence rates of behavioral disorders in children have increased. One factor possibly implied in the etiology of behavioral disorders is exposure to perfluoroalkyl substances (PFASs). The use of PFASs is highly integrated into everyday life, and exposure is ubiquitous. Exposure to PFASs during early life may be particularly harmful, as it represents a critical time window for brain development. However, research in the area is limited, especially among preschool children. The ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 82 publications
(100 reference statements)
0
37
1
Order By: Relevance
“…In this cohort, infants with hypotonic phenotypes had lower psychomotor development and lower externalizing scores at 2–3 years of age [88]. A small Dutch cohort examined 76 children 18 months of age and found no associations between prenatal PFAS exposure and ADHD scores, but externalizing behavior in boys appeared to be related to prenatal PFOA level [86]. Lastly, the Norwegian birth cohort also found no associations between breastmilk levels of PFOS and PFOA and early neuropsychological development at 12 and 24 months [87].…”
Section: Neurodevelopmental Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this cohort, infants with hypotonic phenotypes had lower psychomotor development and lower externalizing scores at 2–3 years of age [88]. A small Dutch cohort examined 76 children 18 months of age and found no associations between prenatal PFAS exposure and ADHD scores, but externalizing behavior in boys appeared to be related to prenatal PFOA level [86]. Lastly, the Norwegian birth cohort also found no associations between breastmilk levels of PFOS and PFOA and early neuropsychological development at 12 and 24 months [87].…”
Section: Neurodevelopmental Effectsmentioning
confidence: 99%
“… The studies in the table are listed according to the continent (in order of America, Europe and Asia), country (alphabetical order) and year of publication. a Three cross-sectional studies [8385], one small study less than 100 subjects [86] and one study that evaluated PFASs in breastmilk [87] are not listed in the table. …”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…neurodevelopmental or neurological effects of PFAS exposure 16,18,[21][22][23] , although recent epidemiological studies indicate an association between PFAS exposure and child behaviour 24,25 . It is important to keep in mind that exposure to PFAS in these studies is continuous and/or based on prolonged exposure paradigms.…”
mentioning
confidence: 99%
“…However, individuals gestationally exposed to PFOA at 10x higher serum concentrations showed increased odds ratio of being categorized as hypotonic rather than social/easygoing. Studies of children from the Swedish cohort or the Dutch cohort Linking Maternal Nutrition to Child Health reported no PFOA exposure-related association with attention deficit hyperactivity disorder (Ode et al, 2014; Quaak et al, 2016). Recent studies with a Danish cohort found no evidence of exposure-related associations between maternal serum concentrations of PFOA and offspring behavioral or affective disorders, including scholastic achievement over a 20-yr follow-up period (Strom et al, 2014) or in increased risk of attention deficit/hyperactivity disorder or autism (Liew et al, 2015).…”
Section: Introductionmentioning
confidence: 99%